FACTORS RELATED TO THE INCIDENT OF STUNTING (ECONOMIC STATUS AND EXCLUSIVE BREASTFEEDING) IN TODDLER AGE 25-59 MONTHS - Metasari, Andi Ria; Sumarni, Sumarni; Kamsiar, Kamsiar (PT. Publikasiku Academic Solution, 2024)
Stunting is one of the problems that hampers human growth and development globally and is a form of malnutrition which is marked by the Z-score of height for age (TB/U). community-based on monthly income, which usually affects the incidence of stunting. In addition, exclusive breastfeeding is only breastfeeding for babies from birth to 6 months of age without being given other food and drinks. The purpose of this study was to determine the relationship between economic factors and exclusive breastfeeding for stunting toddlers aged 25-59 months in the Awangpone District in 2021. This research method used the accidental sampling method according to the inclusion criteria. There are 80 respondents obtained from the results of the chi-square statistical test analysis showing that there is a significant relationship between economic status and exclusive breastfeeding on the incidence of stunting with p = 0.003 and p = 0.002